Improving Student Learning Outcomes through the Use of the Learning Together Learning Model in Integrated Social Studies Subjects - Pein Hiola; Frahmawati Bumulo; Agil Bahsoan; Radia Hafid; Sudirman Sudirman (Badan Penerbit STIEPARI Press, 2025)
This study aims to improve student learning outcomes by implementing the Learning Together instructional model in the Integrated Social Science subject for Grade VIII students at SMP Negeri 3 Kota Gorontalo. The researcher acted as the classroom teacher and was assisted by the subject teacher, who served as an observer The study was conducted in two cycles, each consisting of two class sessions. Each cycle included four stages. planning, implementation, observation, and reflection. Data collection techniques used in this study included observation, teacher activity observation sheets, student activity observation sheets, and documentation, all aimed at measuring improved student learning outcomes. The findings indicated increased student engagement from the initial condition through Cycle 1 and Cycle II. In Cycle II, both teacher and student activity data reached the predetermined success indicator of 80% student learning outcomes. Specifically, teacher activity achieved a 94% score, while student activity also reached 92%. Additionally, a significant improvement was observed in students' academic performance, with learning outcomes increasing from the pretest to the posttest by 93%. These results demonstrate that the Learning Together model effectively enhances student learning outcomes.